Educação infantil no município de Cachoeira do Sul/RS: impasses e perspectivas na formação de professores - Hettwer, Mirian Cristina (2018)
The present study had as objective to know the public policies of children education teachers of the city of Cachoeira do Sul / RS. This is a case study with a qualitative approach, in which the data collection took place through documentary research and the realization of a focus group. The empirical field has been carried out in the city of Cachoeira do Sul / RS at the Kindergarten Pró-Infância - Patrona Marisa Timm Sari. The research subjects are the professionals of this school that is constituted by the directive team, teachers and monitors.The theoretical methodological assumptions that supported and inspired the research were Oliveira-Formosinho (2002) and Kramer, Nunes e Carvalho (2013) to deal with the qualification of children education teachers, specifically. Thus, the proposal of training in context has been carried out according to the studies of Oliveira-Formosinho (2002), with topics suggested by the work group for the formative meetings that were part of the project of formation of this school. The authors of the research were Ariès (2011), Ostetto (2017), Horn (2004), Barbosa (2008), among others. The analyzes carried out in this research revealed that educational policies for early childhood education are on the way to achieving them, reaching the goals set by public policies with expansion of pre-school places, but much remains to be done.We realize that there is a need for specific training for early childhood education, since most professionals have only the minimum qualification of the Normal Course. Through the formative meetings, we realize that teachers need to recognize the child as a powerful subject and of rights, that the spaces must be organized according to the desires and curiosities, that it is necessary to document, to register the pedagogical practice in order to really be able to know the process development. The reflections presented in this Masters Dissertation, developed from the Graduate Program in Public Policies and Educational Management, by the Federal University of Santa Maria, supported by the research line Policies and Management of Basic and Higher Education, help to understand the importance of political perspective to the qualification of the work done with the children, thinking about their rights and respecting their specificities and potentialities. Therefore, the data referring to the municipality will be compiled in the form of a leaflet and the schedule of in-context training will be forwarded to the Municipal Education Department as a product of this study.